Analisis Pengaruh Implementasi Sistem Enterprise Resource Planning (ERP) dalam Meningkatkan Kinerja Perusahaan (Studi Kasus Pada Perum Bulog Kanwil NTB) - Lalu Hendra Maniza; Sudarta Sudarta; Hanifah Muafin; Muhammad Naim; Vici Handalusia Husni (STIE AMKOP, 2023)
This research is intended to analyze the application of the system with the new method of Enterprise Resource Planning (ERP) in web-based logistics planning, reporting and control activities, is there any influence in improving company performance at Perum BULOG KANWIL NTB. With the formulation of the problem of how the effect of Enterprise Resource Planning (ERP) system implementation on improving company performance at Perum BULOG KANWIL NTB. Performance measurement is seen based on the main factors that influence the success of ERP system implementation, namely system quality factors and user involvement factors followed by other factors. ERP implementation at Perum BULOG, especially the NTB Regional Office, is still under development so that the performance measurement of ERP system implementation in this study is only from the perspective of the quality of the information system produced and the performance of individual employees in supporting the success of ERP implementation. This type of research is descriptive quantitative research. The data used in this research is primary data. The data collection method is interviews and questionnaires with user research samples from the ERP system. The test results in this study indicate that Enterprise Resource Planning (ERP) implementation has a significant positive impact on company performance, from the perspective of Information System Quality and Employee Performance perspective after ERP implementation in partial hypothesis testing with the results Ho is rejected and Ha is accepted. Keywords: Enterprise Resource Planning, Information System Quality, and Employee performance